PRECISION AND DISCOUNTED SERVICE. - Thomas, Arthur L. (The Accounting Review, 1962)
Abstract For many years certain accounting theorists have suggested that an asset's value might be measured by the discounted value of its future services. This approach has been given several names, including "time preference analysis," "economic valuation," and "direct valuation." Theorists differ somewhat in the way in which they explain this approach the discounted services approach should be abandoned for theoretical purposes. All we have seen is that it must be imprecise or irrelevant in actual accounting practice. Precision and strict relevance are not necessary qualities in an analytical approach. The approach merely must be able to give us insights into the process this paper is examining. The discounted services approach does this admirably. It fails only when we ask the process examined to model itself on the approach used to examine it. The theorist should feel free to use the discounted services approach whenever it may clarify his thinking. But he should scrupulously avoid using it as a standard of comparison for actual accounting practice.